Public transit and urban poetics: Singapore's Moving Words poetry project and anthology. Issue 2 (1st February 2021) - Gui, Weihsin
ABSTRACT: This essay examines the 2011 Moving Words public poetry campaign in Singapore where poems were displayed in many train stations of the Mass Rapid Transit rail system. It also discusses the poetry anthology, Moving Words, containing poems submitted by members of the public as part of the campaign. While existing studies of Singaporean literature and culture discuss urban space, architecture, and roadways as significant literary tropes, no study of the Mass Rapid Transit's role and representation in poetry exists. In contrast to the Singaporean state's promotion of neoliberal work-driven time-discipline and lifestyles, the Moving Words poems imagine an affective and temporal sphere of social relations that is more capacious and relational. Drawing on Walter Benjamin's idea of distraction and socio-cultural studies of urban life and public transit, I analyse the poems by showing how their form and content appropriate the mechanical and regulated spaces of train stations and carriages to transcend civil inattention and explore alternative temporal rhythms and emotional states. Disrupting the calibrated coercion of Singaporeans as docile passengers and efficient workers, the poems encourage readers to imagine relationships with each other and with the country's past and future that exceed neoliberalism's relentless focus on the present and productivity.